Relationship Between Eating Behaviors and Physical Activity with Blood Glucose Levels in Type 2 Diabetes Mellitus Patients in Gayaman Public Health Center Mojokerto - Erva Heni Rosiana, Erva Heni Rosiana; Ika Ainur Rofi'ah; Moch. Achwandi; Enny Virda Yuniarti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Introduction: Diabetes mellitus can be caused by an unhealthy lifestyle including poor eating behavior and mild physical activity which can affect glucose metabolism so that blood glucose levels are high. This study aims to determine the relationship between eating behavior and physical activity with blood glucose levels in type 2 diabetes mellitus patients. Method: The study design used correlation analysis with a cross-sectional approach. The population in this study was all type 2 diabetes mellitus patients at the Gayaman Public Health Center Mojokerto. The sampling technique of this study was consecutive sampling. The research instrument used an eating behavior questionnaire adopted from the Aethelstone and physical activity level (PAL) questionnaire and was analyzed using the Spearman Rho test. Results: The results showed that 44.6% of respondents had poor eating behaviors, 48.2% had mild physical activity, and 80.4% had high blood glucose levels. The results of the Spearman Rho test showed that there was a significant relationship between eating behavior with blood glucose levels (p value=0,001;α<0,05) and physical activity with blood glucose levels (p value=0,002;α<0,05) in patients with type 2 diabetes mellitus at the Gayaman Public Health Center Mojokerto. Conclusion: Poor eating behaviors tend to cause high blood glucose levels because of excessive intake of food and drinks that contain carbohydrates which are metabolized to be glucose, if the patient is not doing physical activity then the glucose levels become high. The importance of controlling blood glucose levels in Type 2 Diabetes Mellitus patients by improving eating behavior includes an eating schedule, reducing food and drinks that contain a lot of glucose, and increasing physical activity